2016
DOI: 10.1016/j.virusres.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the biology of porcine epidemic diarrhea virus in the era of reverse genetics

Abstract: Emergence of the porcine epidemic diarrhea virus (PEDV) as a global threat to the swine industry underlies the urgent need for deeper understanding of this virus. To date, we have yet to identify functions for all the major gene products, much less grasp their implications for the viral life cycle and pathogenic mechanisms. A major reason is the lack of genetic tools for studying PEDV. In this review, we discuss the reverse genetics approaches that have been successfully used to engineer infectious clones of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 159 publications
(184 reference statements)
0
32
0
Order By: Relevance
“…However, recently, it was demonstrated that PEDV is genetically more closely related to BtCoV/512/2005 than to TGEV, leading to the hypothesis that PEDV may have originated from bats ( Figure 2) [47 ]. Additionally, PEDV infects cells from pigs, humans, monkeys, duck, and bats, further supporting the theory that PEDV had crossed the batswine interspecies barrier sometime in the past (Table 1) [48,49]. PEDV has been detected from feral pigs in Korea and the US [50,51 ], with the latter study suggesting that PEDV may have spilled over from domestic to feral pigs.…”
Section: Origin and Potential For Intra/interspecies Transmissionmentioning
confidence: 75%
“…However, recently, it was demonstrated that PEDV is genetically more closely related to BtCoV/512/2005 than to TGEV, leading to the hypothesis that PEDV may have originated from bats ( Figure 2) [47 ]. Additionally, PEDV infects cells from pigs, humans, monkeys, duck, and bats, further supporting the theory that PEDV had crossed the batswine interspecies barrier sometime in the past (Table 1) [48,49]. PEDV has been detected from feral pigs in Korea and the US [50,51 ], with the latter study suggesting that PEDV may have spilled over from domestic to feral pigs.…”
Section: Origin and Potential For Intra/interspecies Transmissionmentioning
confidence: 75%
“…These mutations probably facilitated the rescue of recombinant viruses in Vero cells but may impair the pathogenicity of recombinant AVCT12 (rAVCT12) in vivo. A review article summarizing different reverse genetics platforms for PEDV was recently published (52).…”
Section: Figmentioning
confidence: 99%
“…Reverse genetics technology provides a useful tool to molecular biology against the pathogenesis of PEDV (47). Although several reverse genetics systems have been established for PEDV (48)(49)(50)(51), its application to identification of virulence determinants has been rare (47,49,52). A recent study reported that a mutant (icPC22A-S1Δ197) bearing a 197-aa deletion in the N-terminal domain of S from an infectious cDNA clone of the highly virulent PEDV PC22A is attenuated in piglets (52).…”
Section: Importancementioning
confidence: 99%